2016
DOI: 10.3892/or.2016.5263
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated truncated Bid overexpression induced by the Cre/LoxP system promotes the cell apoptosis of CD133+ ovarian cancer stem cells

Abstract: Cancer stem cells are a small subset of cancer cells that contribute to cancer progression, metastasis, chemoresistance and recurrence. CD133-positive (CD133+) ovarian cancer cells have been identified as ovarian cancer stem cells. Adenovirus-mediated gene therapy is an innovative therapeutic method for cancer treatment. In the present study, we aimed to develop a new gene therapy to specifically eliminate CD133+ ovarian cancer stem cells by targeting CD133. We used the Cre/LoxP system to augment the selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…For example, CD133, ALDH1, CD44, and CD117 have been used as OCSCs markers [ 24 ]. Amongst the surface markers, CD133 has been proved to be a reliable marker for OCSCs separation in many studies [ 25 , 26 ]. In our study, the CD133 was used as the OCSC surface marker.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CD133, ALDH1, CD44, and CD117 have been used as OCSCs markers [ 24 ]. Amongst the surface markers, CD133 has been proved to be a reliable marker for OCSCs separation in many studies [ 25 , 26 ]. In our study, the CD133 was used as the OCSC surface marker.…”
Section: Discussionmentioning
confidence: 99%
“…Survivin, another anti-apoptotic protein, has been shown to be up-regulated in breast CSCs and to lead to therapeutic resistance of breast CSCs [151]. Targeting Bid, a pro-apoptotic protein, in ovarian CSCs reduced the stemness of these cells, suggesting that Bid is responsible for the elevated stemness in ovarian CSCs [152]. Targeting these pro-apoptotic and anti-apoptotic proteins in CSCs may increase sensitivity of CSCs to drug-mediated cell death.…”
Section: Maintenance Of “Cancer Stemness”mentioning
confidence: 99%
“…They constructed two recombinant adenoviruses, the first facilitates the expression of the Cre in CD133+ CSCs, which cut-off LoxP sequences from the second, thus allowing the overexpression of tBid, driven by the CMV promoter, in CD133+ CSCs. This system induced the apoptosis and inhibited growth of OCSCs in vitro and in vivo, in addition to increasing the cytotoxic effect of cisplatin [ 130 ]. Furthermore, it has been shown that OCSCs expressed several genes related to primordial germ cells, germinal lineage, and pluripotency, such as Nanog, Oct4 and Sox2; therefore, their involvement in the manifestation of OC is not excluded [ 131 ].…”
Section: Future Directionsmentioning
confidence: 99%